Characterization of nonmetallic inclusions in ti stabilized al-killed ultra-low carbon steel - Leão, Pablo Bruno Paiva (2017)
The present work is based on the characterization of nonmetallic inclusions in Ti stabilized ultra-low carbon steel, produced in a large steel mill. Due to a large incidence of submersed valve clogging in a continuous casting, the study is important in order to know the characteristics of the inclusions which are causing the problem. Total of 24 heats were sampled in the tundish and manually analyzed with a scanning electron microscope. The results revealed that 98.65% of the 3183 inclusions analyzed were solid in steelmaking temperature and 66.54% were alumina. The solid inclusions of alumina have low wettability for the iron bath, showing a high tendency of agglomeration in the submersed valves, affecting the castability. It has been concluded from the results and literature that some alternative measures such as the application of the treatment with calcium, precautions to avoid steel re-oxidation and the total or partial replacement of the pre-deoxidized element; would reduce the obstruction problem.